Automation of printing path design for 3D concrete printing using BIM - Gan, Nicole Jia Hui (Nanyang Technological University, 2019)
The construction industry we know today is often critiqued to be too traditional and lacking innovation. This spurs the development of 3D Concrete Printing, which seeks to improve productivity, lower costs and minimise waste, among several other benefits. As it gradually gains traction and becomes increasingly accepted, there exists a need to optimize the design and printing process to aid the widespread adoption of 3D Concrete Printing across the world. While programs for typical 3D Printing are extensive, application is limited for 3D Concrete Printing due to the material properties of concrete. This project therefore seeks to develop a program which would automate the printing path design from Building Information Modelling (BIM) that would be suited for 3D Concrete Printing. At the click of a button, the program would slice the BIM model obtained, generate the printing points along its perimeter and infill, then consolidate the points into a continuous path, and finally translate this path into a G-code file readable by 3D Printers. This research would be the first of its kind, potentially disrupting the current process for 3D Concrete Printing and significantly boosting productivity in this space. In this report, development of the proposed program was discussed in detail. At the end of the process, a 3D Concrete Print job was also arranged to test the viability of the program for closed wall structures. Recommendations for further works were then discussed.